Flame-retardant and anti-aging composite wall material and preparation process thereof

By using ammonia sulfurulan and coupling agents mixed with antioxidants, the problem of weak interaction between antioxidants in composite wall materials is solved, and the stability and durability of the material are improved, and anti -flame retardant and anti -aging aging is enhanced. performance.

CN119349964AInactive Publication Date: 2025-01-24SICHUAN LAN SHANG PIPE IND TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411929940.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing antioxidants have weak interaction forces with inorganic materials in composite wall materials, resulting in easy migration or aggregation of antioxidant molecules, reducing the overall mechanical properties of the material.

Method used

Amifostine thiol and coupling agent are mixed at a molar ratio of 1:1.0 to 1.2 to prepare antioxidants, and the coupling agent is used to improve the interface compatibility between inorganic substances and organic substances and enhance the binding force.

Benefits of technology

It improves the internal bonding strength of the material, reduces the migration of antioxidants, enhances the overall stability and durability of the material, and improves the flame retardant and anti-aging properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of composite wall materials, in particular to a flame-retardant and anti-aging composite wall material and a preparation process thereof. The waterproof coating comprises the following components: 0.5 to 1.5 parts by weight of an antioxidant, 13 to 17 parts by weight of Portland cement, 2 to 4 parts by weight of epoxy resin, 1 to 3 parts by weight of polyurethane, 0.8 to 1.2 parts by weight of an ethylenediamine curing agent, 2 to 6 parts by weight of glass fiber, 4 to 8 parts by weight of aluminum hydroxide, 3 to 11 parts by weight of 2-diphenylphosphine ethanethiol, 2 to 4 parts by weight of a polydimethylsiloxane waterproof agent and 2-(2-diphenylphosphine ethanethiol). The component A comprises the following components in parts by weight: 0.1-0.5 part of 2 '-hydroxy-5'-methylphenyl) benzotriazole, 0.2-0.4 part of lauryl sodium sulfate and 55-65 parts of a fly ash filling material; wherein the antioxidant is prepared by mixing amifostine mercaptan and a coupling agent according to a molar ratio of 1: (1.0-1.2); the coupling agent is prepared by mixing hexamethylene diisocyanate and gamma-glycidyl propyl trimethoxy silane; the curing agent is a mixture of a curing agent and a curing agent; the antioxidant is adopted, so that the anti-aging and flame-retardant effects of the wall material are improved, the interface compatibility is improved, and the stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite wall materials, in particular to an anti-flame retardant and anti-aging composite wall material and a preparation process thereof. Background Art

[0002] Flame retardant and anti-aging composite wall materials are a new type of building material that combines a variety of excellent properties. It combines different materials in the form of a composite structure to achieve significant improvements in fire prevention, heat insulation, durability and environmental protection. It usually contains inorganic materials, which enable the fire resistance level of the wall to reach a higher standard, such as Class A fire resistance, thereby effectively ensuring the safety of the building. Even in a high temperature environment, this wall material can maintain its structural stability and integrity, and is not easy to cause a fire or aggravate the spread of the fire. At the same time, it uses a variety of highly durable materials, such as fiberglass, glass fiber, etc. These materials have excellent anti-aging properties and can effectively resist adverse factors such as weathering and corrosion in the natural environment, thereby extending the service life of the wall. As people's requirements for building safety and environmental protection continue to increase, this wall material will play an increasingly important role in the future construction field.

[0003] However, in most cases, antioxidants are mixed evenly with the matrix material by kneading or blending so that they are evenly distributed throughout the material. This distribution method can ensure that the antioxidant forms an effective protective layer inside the material and alleviates the aging of the wall. However, the interaction between the antioxidant molecules and the inorganic material molecules is weak. Especially when the compatibility between the antioxidant and the matrix material is poor, the antioxidant molecules are more likely to migrate or aggregate from the inside of the material, resulting in an unstable material structure, thereby reducing the overall mechanical properties of the material. In view of this, we propose a flame retardant and anti-aging composite wall material and a preparation process. Summary of the invention

[0004] The object of the present invention is to provide a flame retardant and anti-aging composite wall material and a preparation process to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides a flame retardant and anti-aging composite wall material, comprising the following components: 0.5-1.5 parts by weight of antioxidant, 13-17 parts by weight of silicate cement, 2-4 parts by weight of epoxy resin, 1-3 parts by weight of polyurethane, 0.8-1.2 parts by weight of ethylenediamine curing agent, 2-6 parts by weight of glass fiber, 4-8 parts by weight of aluminum hydroxide, 3-11 parts by weight of 2-diphenylphosphine ethanethiol, 2-4 parts by weight of polydimethylsiloxane waterproofing agent, 0.1-0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.2-0.4 parts by weight of sodium dodecyl sulfate and 55-65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.0-1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and gamma-glycidylpropyltrimethoxysilane.

[0006] Preferably, the preparation method of the antioxidant is as follows: First, add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue to stir and heat at 30-60°C for 2-4 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, then add dibutyltin dilaurate, adjust the pH of the solution with pyridine, heat at 30-40°C with continuous stirring, and react for 4-6 hours. After the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0007] Amifostine thiol has the effects of scavenging free radicals and anti-oxidation. The thiol group has strong reducing properties and can react with free radicals to convert them into stable compounds, thereby scavenging free radicals, reducing material aging caused by oxidation reactions, helping to extend the service life of the material, and reducing performance degradation caused by long-term exposure to the natural environment. Since the dispersibility of organic matter in inorganic matter (substrate) is poor, the interface compatibility between organic matter and matrix material is poor, which easily leads to the migration of organic matter, making the stability of the matrix reduced. At the same time, the dispersion in the matrix material is uneven, forming aggregations. These aggregates will become weak points in the material, thereby reducing the overall mechanical properties of the material. Therefore, a coupling agent is used to react with the amino group of the organic matter through the isocyanate group at one end, and the other end can be combined with the silane group to combine with the hydroxyl group on the surface of the inorganic matter, thereby realizing the coupling effect between the inorganic and organic matter, improving the binding force between the organic and inorganic matter, and improving the dispersibility, interface compatibility and stability of the organic matter in the matrix.

[0008] The coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane. The epoxy group of γ-glycidylpropyltrimethoxysilane can react with an isocyanate group of hexamethylene diisocyanate to form a chemical bond. The intermediate formed in this way has an isocyanate group that can react with organic matter and a silane group that can react with the surface of inorganic matter, that is, the isocyanate group reacts with the amino group of the antioxidant, and the silane group at the other end combines with the hydroxyl group of the inorganic material, so that the inorganic material and the organic material are effectively bridged.

[0009] 2-Diphenylphosphine ethanethiol contains flame-retardant phosphorus atoms, which can promote the formation of a solid carbon layer on the polymer surface under combustion. Since the carbonized layer has good stability and low thermal conductivity, and its structure is relatively dense, it can effectively prevent the diffusion of oxygen, thereby inhibiting the combustion reaction. In addition, phosphorus can generate substances such as phosphoric acid and metaphosphoric acid under high temperature conditions. These acidic substances can form a protective film on the polymer surface, further isolating oxygen and absorbing heat, thereby inhibiting combustion. In a high-temperature environment, it can also decompose to produce PO• free radicals, capture H• and HO• free radicals in the combustion reaction, and slow down the combustion chain reaction, thereby achieving a flame retardant effect.

[0010] Both amifostine thiol and 2-diphenylphosphine ethanethiol contain sulfur groups on their surfaces. The two can combine through the sulfur groups to form a dynamic disulfide bond, which can be reformed when the wall is damaged, thereby giving the material a certain self-repair ability. Self-repairing walls can reduce the need for regular inspections and repairs, reducing long-term maintenance costs. At the same time, by automatically repairing cracks, the structural integrity of the wall can be maintained, preventing them from expanding into larger structural problems, extending their service life and improving safety. More importantly, automatic crack repair helps maintain the sealing of the wall, prevents moisture penetration and improves thermal insulation, greatly improving the durability of the wall.

[0011] Preferably, the mass ratio of the γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:10-20.

[0012] Preferably, the molar ratio of triethylamine to hexamethylene diisocyanate is 0.05-0.07:1.

[0013] Preferably, the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.1-1.3.

[0014] Preferably, the added amount of dibutyltin dilaurate is 0.01-0.05% of the mass of amifostine thiol.

[0015] Preferably, the pyridine solution is adjusted to a pH of 7-9.

[0016] On the other hand, the present invention provides a preparation process of an anti-flame retardant and anti-aging composite wall material, which is used for any one of the anti-flame retardant and anti-aging composite wall materials described above, comprising the following steps: Epoxy resin and polyurethane are premixed, and ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1000-1500rpm. After silicate cement and fly ash filling materials are mixed with water and evenly mixed, antioxidants, polyurethane, 2-diphenylphosphine ethanethiol, polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, epoxy resin and polyurethane premix are added to ensure that the raw materials are evenly mixed. The mixed materials are poured into a mold for curing, and an anti-flame retardant and anti-aging composite wall material is obtained.

[0017] Preferably, the mass ratio of water to silicate cement is 1:0.4-0.6.

[0018] Preferably, the curing temperature is room temperature, the relative humidity is controlled at 51-63%, and the curing time is 12-24 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects: In the flame retardant and anti-aging composite wall material and its preparation process, an antioxidant is prepared by using amifostine thiol and a coupling agent. The ability of amifostine thiol to scavenge free radicals improves the anti-aging effect of the wall material. The coupling agent is used to improve the interface compatibility between amifostine thiol and inorganic materials, enhance the internal bonding strength of the material, reduce the migration of amifostine thiol in the inorganic matrix, and improve the overall stability and durability of the material. In addition, the addition of 2-diphenylphosphine ethanethiol provides additional antioxidant properties on the one hand and increases flame retardant properties on the other hand. At the same time, a dynamic disulfide bond is formed by combining amifostine thiol with the sulfur group of 2-diphenylphosphine ethanethiol, so that the material has a certain self-repairing ability, maintains the integrity and sealing of the wall, and has obvious advantages over traditional wall materials. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] The flame retardant and anti-aging composite wall material of the present invention comprises the following components: 0.5-1.5 parts by weight of antioxidant, 13-17 parts by weight of silicate cement, 2-4 parts by weight of epoxy resin, 1-3 parts by weight of polyurethane, 0.8-1.2 parts by weight of ethylenediamine curing agent, 2-6 parts by weight of glass fiber, 4-8 parts by weight of aluminum hydroxide, 3-11 parts by weight of 2-diphenylphosphine ethanethiol, 2-4 parts by weight of polydimethylsiloxane waterproofing agent, 0.1-0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.2-0.4 parts by weight of sodium dodecyl sulfate and 55-65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.0-1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and gamma-glycidylpropyltrimethoxysilane.

[0022] Embodiment 1: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 1.5 parts by weight of antioxidant, 17 parts by weight of silicate cement, 4 parts by weight of epoxy resin, 3 parts by weight of polyurethane, 1.2 parts by weight of ethylenediamine curing agent, 6 parts by weight of glass fiber, 8 parts by weight of aluminum hydroxide, 11 parts by weight of 2-diphenylphosphinethiol, 4 parts by weight of polydimethylsiloxane waterproofing agent, 0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.4 parts by weight of sodium lauryl sulfate and 65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.0; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:20; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.07:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.3; the addition amount of dibutyltin dilaurate is 0.05% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.6; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0023] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0024] Embodiment 2: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 1.5 parts by weight of antioxidant, 17 parts by weight of silicate cement, 4 parts by weight of epoxy resin, 3 parts by weight of polyurethane, 1.2 parts by weight of ethylenediamine curing agent, 6 parts by weight of glass fiber, 8 parts by weight of aluminum hydroxide, 11 parts by weight of 2-diphenylphosphinethiol, 4 parts by weight of polydimethylsiloxane waterproofing agent, 0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.4 parts by weight of sodium lauryl sulfate and 65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.1; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:20; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.07:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.3; the addition amount of dibutyltin dilaurate is 0.05% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.6; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0025] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0026] Embodiment 3: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 1.5 parts by weight of antioxidant, 17 parts by weight of silicate cement, 4 parts by weight of epoxy resin, 3 parts by weight of polyurethane, 1.2 parts by weight of ethylenediamine curing agent, 6 parts by weight of glass fiber, 8 parts by weight of aluminum hydroxide, 11 parts by weight of 2-diphenylphosphinethiol, 4 parts by weight of polydimethylsiloxane waterproofing agent, 0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.4 parts by weight of sodium lauryl sulfate and 65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:20; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.07:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.3; the addition amount of dibutyltin dilaurate is 0.05% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.6; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0027] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0028] Embodiment 4: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 1.5 parts by weight of antioxidant, 13 parts by weight of silicate cement, 2 parts by weight of epoxy resin, 1 part by weight of polyurethane, 0.8 parts by weight of ethylenediamine curing agent, 2 parts by weight of glass fiber, 4 parts by weight of aluminum hydroxide, 3 parts by weight of 2-diphenylphosphinethiol, 2 parts by weight of polydimethylsiloxane waterproofing agent, 0.1 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.2 parts by weight of sodium lauryl sulfate and 55 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:10; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.05:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.1; the addition amount of dibutyltin dilaurate is 0.01% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.4; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0029] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0030] Embodiment 5: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 0.5 parts by weight of antioxidant, 17 parts by weight of silicate cement, 4 parts by weight of epoxy resin, 3 parts by weight of polyurethane, 1.2 parts by weight of ethylenediamine curing agent, 6 parts by weight of glass fiber, 8 parts by weight of aluminum hydroxide, 11 parts by weight of 2-diphenylphosphinethiol, 4 parts by weight of polydimethylsiloxane waterproofing agent, 0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.4 parts by weight of sodium lauryl sulfate and 65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:20; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.07:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.3; the addition amount of dibutyltin dilaurate is 0.05% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.6; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0031] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0032] Embodiment 6: A flame retardant and anti-aging composite wall material and a preparation process, comprising the following steps: Prepare components: 1.0 parts by weight of antioxidant, 17 parts by weight of silicate cement, 4 parts by weight of epoxy resin, 3 parts by weight of polyurethane, 1.2 parts by weight of ethylenediamine curing agent, 6 parts by weight of glass fiber, 8 parts by weight of aluminum hydroxide, 11 parts by weight of 2-diphenylphosphinethiol, 4 parts by weight of polydimethylsiloxane waterproofing agent, 0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.4 parts by weight of sodium lauryl sulfate and 65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.2; the coupling agent is prepared by mixing hexamethylene diisocyanate and γ-glycidylpropyltrimethoxysilane; the mass ratio of γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:20; the molar ratio of triethylamine to hexamethylene diisocyanate is 0.07:1; the molar ratio of hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.3; the addition amount of dibutyltin dilaurate is 0.05% of the mass of amifostine thiol; the mass ratio of water to silicate cement is 1:0.6; First add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue stirring and heat at 45°C for 2 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, and then add dibutyltin dilaurate, adjust the solution pH to 7 with pyridine, heat at 30°C and continue stirring, the reaction time is 4 hours, after the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

[0033] The epoxy resin and the polyurethane are premixed, and an ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1200 rpm. After the silicate cement and the fly ash filling material are mixed with water and uniformly, an antioxidant, a polyurethane, 2-diphenylphosphine ethanethiol, a polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, the epoxy resin and the polyurethane premix are added to ensure that the raw materials are uniformly mixed. The mixed material is poured into a mold for curing. The curing temperature is room temperature curing, the relative humidity is controlled at 55%, and the curing time is 24 hours to obtain an anti-flame retardant and anti-aging composite wall material.

[0034] Comparative Example 1: The method of Example 3 was adopted without adding an antioxidant.

[0035] Comparative Example 2: The method of Example 3 was adopted, and amifostine thiol was directly added without adding a coupling agent for mixing.

[0036] Comparative Example 3: The method of Example 3 was adopted, and the coupling agent was directly added without adding amifostine thiol for mixing.

[0037] The present invention adopts an anti-flame retardant and anti-aging composite wall material prepared by using an antioxidant, wherein the performance index inspection items and inspection standards of the anti-flame retardant and anti-aging composite wall material are as follows: The limiting oxygen index refers to the minimum oxygen concentration that just maintains the combustion of the material when a mixed gas of oxygen and nitrogen at 23℃±2℃ is introduced. It is expressed as a volume fraction. First, prepare a sample with a specification of 100mm×6.5mm×3mm. Refer to the method of GB-T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method" to measure the limiting oxygen index of the sample and judge the flame retardant performance of the sample. Fix a sample vertically in a transparent combustion chamber of an upward flowing oxygen and nitrogen mixed gas, ignite the top of the sample, observe the combustion characteristics of the sample, and estimate the minimum oxygen concentration.

[0038] Impact resistance can characterize the mechanical strength of the material. Place the impact tester on a stable platform with the guide tube perpendicular to the horizontal plane. Adjust the weight of the impact tester to a certain height through the weight controller. The weight is (1000±1) g. The steel ball on the punch has a diameter of (8.000±0.015) mm and a hardness (HRC) of 61~66. The depth of the punch entering the groove is (2.0±0.1) mm. The die groove should be smooth with a diameter of (15.0±0.3) mm and a radius of curvature of the groove edge of 2.5 mm. m-3.0mm, the distance between the edge of the specimen at the impact point and the edge of the specimen shall not be less than 10mm, the distance between the edges of adjacent impact points shall not be less than 10mm, the specimen size is 120mm×10mm×3mm, press the control button of the weight controller, the weight falls freely on the punch, observe whether the specimen has cracks, if no cracks are observed, repeat the test at higher positions until cracks are observed, the height increased each time is 5cm or a multiple of 5cm, record the maximum height at which no cracks are observed in three tests.

[0039] The samples were subjected to accelerated aging tests using a climate aging chamber, with an aging temperature of 80°C, a relative humidity of 60%, a radiation intensity of 1.2W / m² in the 350nm band of ultraviolet light, and an irradiation time of 8h. The change rate of the impact resistance was then tested, aging change rate = (initial impact resistance - impact resistance after aging) / initial impact resistance × 100%.

[0040] According to the above standards, the flame retardant and anti-aging composite wall materials prepared in the above Examples 1-6 and Comparative Examples 1-3 were tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3 The above data fully show that compared with Comparative Examples 1-3, Examples 1-6 can fully show the effect of antioxidants on the anti-aging, anti-flame retardant and mechanical properties of an anti-flame retardant and anti-aging composite wall material.

[0041] Since the present invention adopts an antioxidant to prepare an anti-flame retardant and anti-aging composite wall material, the performance of the anti-flame retardant and anti-aging composite wall material is effectively improved by the antioxidant, as follows: It can be seen from Examples 1-3 that with the continuous change in the proportion of the antioxidant component, the flame retardant and aging-resistant composite wall materials are significantly improved in terms of anti-aging, flame retardant and mechanical properties. This is because with the continuous increase in the content of the coupling agent, the compatibility between organic and inorganic substances is effectively improved, the migration of organic matter in the inorganic matrix is ​​reduced, and the antioxidant is more evenly distributed in the material, thereby improving its anti-aging effect. The antioxidant and 2-diphenylphosphine ethanethiol are connected by a disulfide bond, which also indirectly improves the stable dispersion of 2-diphenylphosphine ethanethiol as a flame retardant in the substrate, thereby improving its anti-flame retardant effect. The reasonable use of antioxidants and coupling agents improves the dispersibility and compatibility of the components inside the material, reduces defects and pores, and makes the microstructure of the material denser, thereby improving the mechanical properties.

[0042] It can be seen from Examples 3 and 4 that with the continuous change of the content of other materials in the flame retardant and aging-resistant composite wall materials, the flame retardant and aging-resistant composite wall materials have no obvious changes in anti-aging, flame retardant and mechanical properties. This is because antioxidants are the main factors affecting the anti-aging properties of materials, and small changes in the content of other components within a certain range are not enough to affect the overall performance of the composite wall materials. Therefore, there are small changes in anti-aging, flame retardant and mechanical properties.

[0043] It can be seen from Examples 3, 5 and 6 that with the continuous change of the antioxidant content, the flame retardant and aging resistant composite wall materials are constantly changing in terms of anti-aging, flame retardant and mechanical properties. This is because the main function of the antioxidant is to remove free radicals and prevent the material from being degraded due to oxidation. With the increase of the antioxidant content, its concentration in the material increases, which can more effectively capture free radicals, thereby delaying the aging process of the material. Since the antioxidant itself still contains phosphorus elements with flame retardant effects, it can promote the formation of a carbonized layer at high temperatures, thereby enhancing the flame retardant properties. At the same time, the antioxidant can improve the combination of inorganic materials and organic materials, improve the microstructure of the material, make it denser, and thus improve the mechanical properties of the material.

[0044] According to the above test experiments, the flame retardant and anti-aging composite wall material prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-3, it can be seen that: In comparative example 1, no antioxidant is added, and the flame retardant and aging-resistant composite wall material is worse in terms of anti-aging, flame retardant and mechanical properties. This is because free radicals are highly active molecules that can easily trigger oxidation reactions, leading to material aging. Without antioxidants, free radicals will accumulate more easily, accelerating the aging process of the material, and the oxidation reaction triggered by free radicals will cause the breakage of the polymer chain and destroy the microstructure of the material, thereby reducing the physical and mechanical properties of the material. The coupling agent in the antioxidant can improve the interfacial compatibility between organic and inorganic substances. The lack of antioxidants will lead to weaker bonding between organic and inorganic substances, and reduced durability and stability of the material.

[0045] In Comparative Example 2, amifostine thiol is directly added without adding a coupling agent for mixing and preparation. The flame retardant and anti-aging composite wall material is poor in anti-aging, flame retardant and mechanical properties. This is because although amifostine thiol itself has the ability to scavenge free radicals and contains phosphorus atoms with anti-flame retardant effect, in the absence of a coupling agent, it is unevenly distributed in the material and is easy to aggregate or migrate, resulting in a significant reduction in its antioxidant effect, a decrease in the stability of the material, a decrease in mechanical properties, and a weakened anti-flame retardant effect.

[0046] In Comparative Example 3, coupling agent was directly added without adding amifostine thiol for mixing. The flame retardant and anti-aging composite wall material had poor anti-aging, flame retardant and mechanical properties. This is because the coupling agent can improve the dispersibility of antioxidants and flame retardants in inorganic materials, improve interface compatibility, and avoid migration or aggregation that causes the mechanical properties of the material to deteriorate. Therefore, only coupling agent without antioxidant cannot play the key anti-aging function, thereby causing the overall performance of the material to deteriorate.

[0047] In summary, the antioxidant is prepared by mixing amifostine thiol and a coupling agent, which utilizes the antioxidant effect of amifostine thiol and combines the ability of the coupling agent to improve interface compatibility, which not only improves the binding force between amifostine thiol and 2-diphenylphosphine ethanethiol between inorganic materials, but also effectively reduces the internal gap of the material, enhances the density of the material, and improves the mechanical strength of the material. On the one hand, it can more effectively exert the antioxidant and flame retardant effects. On the other hand, through the combination of amifostine thiol and the sulfur group of 2-diphenylphosphine ethanethiol to form a dynamic disulfide bond, the material has a certain self-repairing ability, maintains the integrity and sealing of the wall, and reduces the maintenance cost.

[0048] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A flame retardant and anti-aging composite wall material, characterized in that: The invention comprises the following components: 0.5-1.5 parts by weight of antioxidant, 13-17 parts by weight of silicate cement, 2-4 parts by weight of epoxy resin, 1-3 parts by weight of polyurethane, 0.8-1.2 parts by weight of ethylenediamine curing agent, 2-6 parts by weight of glass fiber, 4-8 parts by weight of aluminum hydroxide, 3-11 parts by weight of 2-diphenylphosphine ethanethiol, 2-4 parts by weight of polydimethylsiloxane waterproofing agent, 0.1-0.5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 0.2-0.4 parts by weight of sodium lauryl sulfate and 55-65 parts by weight of fly ash filling material; The antioxidant is prepared by mixing amifostine thiol and a coupling agent in a molar ratio of 1:1.0 to 1.2; The coupling agent is prepared by mixing hexamethylene diisocyanate and gamma-glycidylpropyltrimethoxysilane.

2. The flame retardant and anti-aging composite wall material according to claim 1, characterized in that: The preparation method of the antioxidant is as follows: First, add γ-glycidylpropyltrimethoxysilane to tetrahydrofuran, then add triethylamine catalyst, and then add hexamethylene diisocyanate dropwise into the γ-glycidylpropyltrimethoxysilane solution, under nitrogen protection, continue to stir and heat at 30-60°C for 2-4 hours. After the reaction is completed, remove the solvent by distillation to obtain a coupling agent; dissolve the coupling agent in anhydrous ethanol, add amifostine thiol, then add dibutyltin dilaurate, adjust the pH of the solution with pyridine, heat at 30-40°C with continuous stirring, and react for 4-6 hours. After the reaction is completed, evaporate and remove the solvent again to obtain an antioxidant.

3. The flame retardant and anti-aging composite wall material according to claim 2, characterized in that: The mass ratio of the γ-glycidylpropyltrimethoxysilane to tetrahydrofuran is 1:10-20.

4. The flame retardant and anti-aging composite wall material according to claim 2, characterized in that: The molar ratio of the triethylamine to hexamethylene diisocyanate is 0.05-0.07:

1.

5. The flame retardant and anti-aging composite wall material according to claim 2, characterized in that: The molar ratio of the hexamethylene diisocyanate to γ-glycidylpropyltrimethoxysilane is 1:1.1-1.

3.

6. The flame retardant and anti-aging composite wall material according to claim 2, characterized in that: The added amount of dibutyltin dilaurate is 0.01-0.05% of the mass of amifostine thiol.

7. The flame retardant and anti-aging composite wall material according to claim 2, characterized in that: The pyridine solution is adjusted to a pH of 7-9.

8. A process for preparing a flame retardant and anti-aging composite wall material, used for preparing the flame retardant and anti-aging composite wall material according to any one of claims 1 to 7, characterized in that: The steps include: Epoxy resin and polyurethane are premixed, and ethylenediamine curing agent is added. A high-speed stirrer is used with a stirring speed of 1000-1500rpm. After silicate cement and fly ash filling materials are mixed with water and evenly mixed, antioxidants, polyurethane, 2-diphenylphosphine ethanethiol, polydimethylsiloxane waterproofing agent, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and sodium dodecyl sulfate are added in sequence, and stirring is continued during the process. Finally, epoxy resin and polyurethane premix are added to ensure that the raw materials are evenly mixed. The mixed materials are poured into a mold for curing, and an anti-flame retardant and anti-aging composite wall material is obtained.

9. The preparation process of a flame retardant and anti-aging composite wall material according to claim 8, characterized in that: The mass ratio of water to silicate cement is 1:0.4-0.

6.

10. The preparation process of the flame retardant and anti-aging composite wall material according to claim 8, characterized in that: The curing temperature is room temperature, the relative humidity is controlled at 51-63%, and the curing time is 12-24 hours.

Citation Information

Patent Citations

  • Fiber cement firewall

    CN103408271A